2010
DOI: 10.1093/jac/dkq114
|View full text |Cite
|
Sign up to set email alerts
|

Signature gene expression profile of triclosan-resistant Escherichia coli

Abstract: These results strongly indicate that E. coli IFN cells might protect themselves from triclosan by activating various defence mechanisms, such as (i) changing efflux activities; (ii) capturing the triclosan; and (iii) increasing the expression of important regulators or metabolic enzymes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Karatzas et al (2007) isolated a triclosan tolerant Salmonella mutant with a 2000 fold increase in its MIC by gradually increasing concentrations of triclosan for 16 days. Yu, Kim, and Pan (2010) isolated triclosan resistant E. coli mutants with the MIC increasing from 6 to 40e80 mg/ml. Braoudaki and Hilton (2004a) showed that the MIC of triclosan increased from 0.25 to 1024 mg/ml in E. coli O157, 0.25 to 2048 mg/ml in E. coli K-12 and from 1 to 2048 mg/ml in E. coli O55:H7.…”
Section: Discussionmentioning
confidence: 99%
“…Karatzas et al (2007) isolated a triclosan tolerant Salmonella mutant with a 2000 fold increase in its MIC by gradually increasing concentrations of triclosan for 16 days. Yu, Kim, and Pan (2010) isolated triclosan resistant E. coli mutants with the MIC increasing from 6 to 40e80 mg/ml. Braoudaki and Hilton (2004a) showed that the MIC of triclosan increased from 0.25 to 1024 mg/ml in E. coli O157, 0.25 to 2048 mg/ml in E. coli K-12 and from 1 to 2048 mg/ml in E. coli O55:H7.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have shown there are also other mechanisms which may infer triclosan resistance, including efflux mechanisms which pump the triclosan out of the cell, capture of the triclosan to prevent it affecting the cell and oyer expression of important enzymes and metabolic regulators (Yu et al 2010).…”
Section: At High Concentrations Triclosan Acts Against Most Susceptibmentioning
confidence: 99%
“…Triclosan was chosen as it has already been incorporated into a number of dentifrices and its anti inflammatory properties, in addition to its action as an antimicrobial, make it a potentially useful substance in controlling pulpal disease (Mustafa et al 1998). Whilst the effect of triclosan has been studied on many organisms such as Pseudomonas aeruginosa (Escalada et al 2005), Escherichia coli (Yu et al 2010) and…”
Section: Introductionmentioning
confidence: 99%
“…36,37,75,76 Of the seven variants, only four had measurable activity, F93V, R96M, R96G, and F203L (Table 1). The F93V and F203L variants had significant reductions in activity (126−190-fold reduction in k cat ).…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%